The Riba Dilemma: How Divergent Perceptions of Bank Interest Shape Muslim Entrepreneurs' Business Strategies - Sudana, Sudana; Marlina, Lina; Dermawan, Muhammad Jagat (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
This study explores the diverse perceptions among Muslim entrepreneurs in Indonesia regarding bank interest and its influence on business decision-making. While some entrepreneurs view bank interest as usury (haram interest), which is prohibited in Islam, others do not, resulting in very different business strategies. Using a qualitative phenomenological approach, data was collected through in-depth interviews with purposively selected participants and analysed using NVivo. The findings reveal two distinct perspectives. The first group views bank interest as Riba, and their business decisions actively avoid conventional banking facilities. They prefer self-financing or community-based financing with profit-sharing principles, are more selective in choosing business partners, and may delay expansion. This group views the difference between Islamic banks and conventional banks as merely a difference in terminology and maintains strong community ties with relatively low financial pressure. This study reveals the evolution of public perception regarding usury in the modern financial system, highlighting how religious interpretations adapt to contemporary economic dynamics while influencing the financial behaviour of the faithful.